Pengaruh “FoMO” Terhadap Perilaku Berbusana pada Generasi Z Melalui Platform Media Sosial Tiktok: Followers @Sasfhir - Yusuf Maulana; Lubis, Nisa Marsellida; Ramadhani, Rizky Wulan; Sri Wahyuni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
Social media plays a central role in shaping the preferences and behaviors of Generation Z, including in the realm of fashion. The TikTok account @sashfir has emerged as a popular source of inspiration among this demographic, particularly in presenting fashion-related content. This study aims to examine the influence of Fear of Missing Out (FoMO) on the fashion behavior of Generation Z followers of the account. A quantitative approach was employed, using a survey method with 100 respondents selected through the Taro Yamane formula. Data were analyzed using simple linear regression. The results show that FoMO has a positive and significant effect on the fashion behavior of @sashfir's followers. The higher the level of FoMO experienced, the greater the tendency to follow fashion trends featured on the account. These findings highlight the relevance of the Uses and Effects theory in explaining the relationship between social media use and behavioral changes among young audiences, particularly in the context of fashion consumption.